2019
DOI: 10.1055/s-0039-3402043
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Knee Arthroplasty in a Knee Osteoarthritis Patient Cohort Treated with Intra-articular Injections of Hylan G-F 20

Abstract: Hylan G-F 20 viscosupplementation can be used to treat knee osteoarthritis pain. This study evaluated time to knee arthroplasty (KA), KA risk factors, and health care resource utilization in patients aged ≥18 years with claims in the Optum Clinformatics Data Mart database (2006–2016) for knee osteoarthritis treated with at least one course of hylan G-F 20. Kaplan–Meier analysis estimated KA risk from osteoarthritis diagnosis and first hylan G-F 20 treatment. KA risk factors were determined using multivariate C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
2
0
1
Order By: Relevance
“…Several studies evaluated the impact of knee OA treatment with IAHA on time to TKA. [23][24][25][26][27] Each of these studies concluded that the use of IAHA is associated with longer time to TKA (Table 2). A retrospective analysis of data from 2006 to 2016 in the Optum Clinformatics database by Ong et al 25 reported a longer median time to TKA of ~7 months for those who received IAHA versus those who did not.…”
Section: Impact Of Iaha On Tkamentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies evaluated the impact of knee OA treatment with IAHA on time to TKA. [23][24][25][26][27] Each of these studies concluded that the use of IAHA is associated with longer time to TKA (Table 2). A retrospective analysis of data from 2006 to 2016 in the Optum Clinformatics database by Ong et al 25 reported a longer median time to TKA of ~7 months for those who received IAHA versus those who did not.…”
Section: Impact Of Iaha On Tkamentioning
confidence: 99%
“…This finding was confirmed in a second retrospective analysis of the Optum Clinformatics database (data from 2006 to 2016) in which the median time from first IAHA treatment to TKA was ~6 months with 1 treatment and approximately 4 years with ⩾5 treatments. 27 Altman et al 23 found that IAHA injections are associated with dose-dependent increase in time to TKA: the mean time to TKA for patients receiving no IAHA was 0.7 years and was 3.6 years for patients who received ⩾5 courses.…”
Section: Impact Of Iaha On Tkamentioning
confidence: 99%
“…Los principales síntomas que caracterizan a la OA son el dolor, la rigidez, la incapacidad funcional, la inestabilidad articular y la inflamación 3 . El resultado de toda esta sintomatología es una disminución de la calidad de vida, un aumento del riesgo de la morbimortalidad y un mayor coste sanitario 4 .…”
Section: Introductionunclassified